Enrichment, Isolation and Characterization of Heavy Metal-Tolerant Bacteria from Polar Lacustrine Sediments - Alessandro C. Rappazzo; Alessia Marchetta; Carmen Rizzo; Maurizio Azzaro; Warren R. L. Cairns; Angelina Lo Giudice; Maria Papale (Microorganisms)
Polar areas are not exempt from anthropogenic pollution. Heavy metals have been detected in Arctic and Antarctic lakes. Bacteria, at the base of the food web, can possess the ability to adsorb or immobilize heavy metals in the environment and reduce their concentration in the water column. However, several gaps exist in our knowledge of bacterial tolerance to heavy metals in polar systems, especially in lakes. Heavy metal-tolerant bacteria from polar lacustrine sediments were selectively enriched and subsequently isolated and identified. Their growth at increasing concentrations of different heavy metals (iron, copper, and mercury) was evaluated. Selected isolates were tested for sequestration of iron and mercury. A total of 101 bacterial isolates were obtained from metal-enriched cultures. Gammaproteobacteria and Actinomycetota isolates were most abundant in Arctic and Antarctic enrichments, respectively. Iron was the most tolerated metal. Mercury and iron were sequestered by the isolates by up to 14.2 and 13.4%, respectively. The results from this study contribute to our understanding of heavy metal-tolerant bacteria from cold environments and their potential use in biotechnological applications.